Evaluating the Effectiveness of Integrated Pest Management with Farmer Field School (IPM/FFS) Approach in Iran - Hassanpour, Behrooz; Kavoosi, Bijan; Saeedi, Karim; Keshavarz, Kavoos (Asian Journal of Biological and Life Sciences, 2017)
Integrated pest management with farmer field school approach (IPM/FFS) is a participatory extension approach implemented in several years to protect the environment and control pests and plant diseases in the agricultural sector of the country. The main objective of this study was to evaluate extension programs of farmer field school in promoting knowledge, skills and attitude of farmers participating in these programs compared with farmers participating in traditional teacher-centered extension classes. The method of study is survey research and cross-correlation with a comparative approach. The study population consisted of two distinct groups of farmers. The first group of farmers participated FFS extension classes and the second group of farmers participated in the traditional teacher-centered classes. From the first group of study, 97 people and from the second group of study, 98 people were randomly selected. Data were collected through questionnaire and interview with farmers and forming discussion discussions with presence of experts and facilitators of participating in programs of the IPM/FFS. Face validity was confirmed by agricultural specialists, and the reliability of questionnaire was confirmed by Chronbach’s Alpha coefficient (79.0 to 91.0). The results of this study showed that the degree of effectiveness of the IPM/FFS’s programs was as “good” criteria from the perspective of farmers. In addition, the level of knowledge, skill and attitude of farmers participated in extension programs of the IPM/FFS’s programs were more than teacher-centered extension courses, and its differences in the level of one percent error (P=0.01) is significant.
Keywords: Agricultural Extension; Attitude; Effectiveness; FFS; IPM; Knowledge; Skill